Experimental verification of coverage control of multi‐agent systems with obstacle avoidance - Fidelia Chaitra Siri; Jie Song; Mikhail Svinin (The Journal of Engineering)
Abstract Multi‐agent systems are a significant and popular area of study in robotics, focusing on efficient and safe coordination among multiple agents. This paper presents algorithms for safe coverage control in multi‐agent systems, addressing key challenges such as coverage control and obstacle avoidance. The coverage control problem is tackled using centroidal Voronoi tessellation with a time‐varying density function, which optimally distributes agents based on the spatial density of the area of interest. To ensure collision‐free manoeuvres, a control barrier function based controller is developed for obstacle avoidance. The proposed controller's effectiveness is validated through a custom Python simulator and experimental tests conducted in the robot operating system–Gazebo environment. The results demonstrate the efficacy of the centroidal Voronoi tessellation and control barrier function approaches in achieving both optimal agent distribution and robust obstacle avoidance.